Imaging Recommendations for Diagnosis, Staging, and Management of Bone Tumors - Janu, Amit; Patra, Anurima; Kumar, Mahesh; Gulia, Ashish; Kulkarni, Suyash; Shetty, Nitin Sudhakar; Puri, Ajay; Nayak, Prakash; Pruthi, Manish (Indian Journal of Medical and Paediatric Oncology, 2023)
Primary bone sarcomas account for less than 1% of diagnosed cancers each year. In this era of multiplanar and functional imaging, the approach to the radiographic diagnosis of bone cancers goes much beyond traditional radiography. Radiographs are still the most pertinent part of the initial diagnosis of bone tumors. Multimodal imaging, such as computed tomography (CT) and magnetic resonance imaging (MRI), can help with issues such as complex anatomy, marrow assessment, soft assessment, and better local staging. The emerging imaging modality such as positron emission tomography (PET)-CT/PET-MRI has further transformed the imaging of bone malignancies. Radiologist plays an important role in the workup, staging, and management of bone tumors. The purpose of this article is to review imaging recommendations for better diagnosis, staging, and management of bone tumors.
Keywords: bone tumor; imaging; management; MRI; radiograph; radiology; staging